Pengaruh Penyaluran Kredit Usaha Pedesaan dan Peran Kredit Usaha Rakyat Terhadap Perkembangan UMKM Pada PT Bank Rakyat Indonesia (PERSERO),Tbk. Unit Jati Mulyo - Amelia Anwar (Universitas Mitra Indonesia, 2021)
This study aims to determine the effect of rural business credit, people’s business credit against the development of UMKM at PT Bank People Indonesian (Persero),Tbk. Mulyo Teak Unit. The data used in this report are primary data namely data obtained directly from the source, spread to respondents. Rural business loan customer 50 people, people’s business credit customers 50 people at PT Bank Rakyat Indonesian (Persero),Tbk. Unit Jati Mulyo. The results in this study indicate that influence rural business credit significantly positive influence on the development of UMKM this can be seen from the results of the t test results of significance value are 0,000 0,05 with t count 8,139 ttable 1,984, the effect of people’s business credit significantly positive influence on the development of UMKM this can be seen from the results of the t with the significance is 0,001 0,05 from the fcalculated value 3,524 ttable 1,984, the influence rural business credit, people business credit against the development of UMKM this can be seen from the test results test f as big 0,000b 0,05 from the fcalculated value 144,043 ftable 3.09. Thus it can be concluded that the variable of rural business credit distribution for, people’s business credit simultaneously has a significant effect o the development of UMKM Keyword: rural business credit, people’s business credit, the development of UMKM